2020
DOI: 10.2147/cmar.s254815
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Circ_0007031 Serves as a Sponge of miR-760 to Regulate the Growth and Chemoradiotherapy Resistance of Colorectal Cancer via Regulating DCP1A</p>

Abstract: Background: Colorectal cancer (CRC) is a kind of malignant tumor, and the development of chemoradiotherapy resistance (CRR) increases the difficulty of its treatment. The role of circular RNAs (circRNAs) in cancer progression has been well documented. Nevertheless, the function of circ_0007031 in the growth and CRR of CRC has not been well elucidated. Methods: CRR cell lines were constructed using 5-Fu and radiation. Cell counting kit 8 (CCK8) assay was employed to measure the 5-Fu resistance and proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“… 17 Moreover, miR-760 could regulate the chemoresistance of cancers through lncRNA KCNQ1OT1/miR-760/PPP1R1B axis, 35 miR-760/ITGB1 axis 16 and circ_0007031/miR-760/DCP1A axis. 15 However, it remains unclear about the effects and regulatory mechanisms of miR-760 in DXR resistance in OS. Our data indicated that miR-760 downregulation abated the suppressive roles of circPRDM2 knockdown in DXR resistance and cell malignant characteristics in DXR-resistant OS cells, indicating circPRDM2 enhanced DXR resistance by sponging miR-760.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 Moreover, miR-760 could regulate the chemoresistance of cancers through lncRNA KCNQ1OT1/miR-760/PPP1R1B axis, 35 miR-760/ITGB1 axis 16 and circ_0007031/miR-760/DCP1A axis. 15 However, it remains unclear about the effects and regulatory mechanisms of miR-760 in DXR resistance in OS. Our data indicated that miR-760 downregulation abated the suppressive roles of circPRDM2 knockdown in DXR resistance and cell malignant characteristics in DXR-resistant OS cells, indicating circPRDM2 enhanced DXR resistance by sponging miR-760.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Wang et al confirmed that miR-760 repressed colorectal cancer (CRC) progression and 5-FU resistance by targeting DCP1A. 15 Yang et al unraveled that miR-760 was able to decrease gemcitabine resistance in pancreatic cancer by binding to ITGB1. 16 In OS, Yin et al demonstrated that miR-760 served as a tumor inhibitor via interacting with HDGF.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, authors claim that high expression of circPRKDC increases β-catenin and c-Myc levels, leading to activation of Wnt/βcatenin pathway in 5-FU resistant CRC cells via miR-375 deletion or FOXM1 (Forkhead box protein M1) overexpression [ 214 ]. Hsa_circ_0007031 is proven as upregulated in 5-FU chemoradiation-resistant CRC cells [ 215 , 216 ], and in 5-FU resistant cell lines [ 217 ]. Xiong et al, 2017 [ 215 ] first bioinformatically predicted signaling pathways involving hsa_circ_0007031, and then Wang et al, 2020 [ 216 ] and He et al, 2020 [ 217 ] presented functional roles of the cicrRNA and proved its notability as a target for overcoming 5-FU and radiation resistance in CRC.…”
Section: Oncogenic Functions Of Circrnasmentioning
confidence: 99%
“…Hsa_circ_0007031 is proven as upregulated in 5-FU chemoradiation-resistant CRC cells [ 215 , 216 ], and in 5-FU resistant cell lines [ 217 ]. Xiong et al, 2017 [ 215 ] first bioinformatically predicted signaling pathways involving hsa_circ_0007031, and then Wang et al, 2020 [ 216 ] and He et al, 2020 [ 217 ] presented functional roles of the cicrRNA and proved its notability as a target for overcoming 5-FU and radiation resistance in CRC. He et al, 2020 [ 217 ] described the sponging of miR-133b followed by increasing expression of ABCC5 (ATP-binding cassette subfamily C member 5) as a mechanism involving hsa_circ_0007031 in 5-FU resistance, while Wang et al, 2020, [ 216 ] reported the miR-760/DCP1A axis as an underlying mechanism of hsa_circ_0007031 action.…”
Section: Oncogenic Functions Of Circrnasmentioning
confidence: 99%
See 1 more Smart Citation